The Genus Pulsatilla : A Review - Kumar, Suresh; Madaan, Reecha; Farooq, Asim; Sharma, Anupam (Pharmacognosy Reviews)
The review includes 84 references on the genus Pulsatilla, and comprises ethnopharmacology, morphology, phytoconstituents, pharmacological reports, clinical study and adverse effects of the prominent species of Pulsatilla. Triterpenoid saponins and flavonoids constitute major classes of phytoconstituents of the genus. A few species of this genus have medicinal value, among these, P. nigricans Stoerck. (family Ranunculaceae) has been traditionally used in the treatment of nervous disorders, and as a remedy for ovaritis, ovaralgia and sexual debility. Despite a long tradition of use of some species, the genus has not been explored properly. In the concluding part, the future scope of Pulsatilla species, especially P. nigricans, has been emphasized with a view to isolate bioactive moieties which could be used for multifarious biological activities.
Keywords: Pharmacology; Pulsatilla; Pulsatilla nigricans; Triterpenoid saponins